EFEKTIVITAS SIDANG KELILING DALAM PENYELESAIAN PERKARA CERAI GUGAT DI PENGADILAN AGAMA SUNGAI RAYA - Mursyid, Mursyid; Hasan, Muhammad; Hakimah, Nur (Al-Usroh, 2023)
The purposeoof this research isito find out: 1). The effectiveness of the implementation of the circuit court at the Sungai Raya Religious Court. 2). The effectivenesss of case settlement throughha circuit courtiat the Sungai Raya Religious Court in 2021. This study uses a qualitative method with an empirical type. Sources of data are primary data through interviews with clerks, substitute clerks and judges. While secondary data is taken from literature related to this research, such as Supreme Court Regulation Number 1 of 2014 concerning Guidelines for Legal Services for the Poor and Supreme Court Circular Number 10 of 2010 concerning Guidelines for Legal Services in Religious Courts. Data collection techniquessare interviewssand documentation.aThe data collection toollused by the researcher is an interview guide. While the data analysis techniques researchers use data reduction, data presentation and drawing conclusions. Then the validity of the data is checked by member checking method. The results showedethat: 1). The effectiveness of the circuit court implementation can be seen from the implementation procedures that can reduce the queues of cases that accumulate at the Sungai Raya Religious Court Office. As for service users, the perceived benefit is a closer distance. So that it can be said that the circuit court is effective in terms of the procedures for its implementation. 2). Judging from the settlement of the case, it can be seen from the handlingeof cases that are relatively few and do not require a long time so that they are more relaxed in completing the settlement of cases that are resolved through mediation. In addition, the effectiveness of the settlement can be seen in the financing where service users are more efficient in transportation to the location. So that the trial can be opened to run effectively from the settlement of the case is enough.